Moisture adsorption properties and shelf-life estimation of dried and pulverised edible house cricket Acheta domesticus (L.) and black soldier fly larvae Hermetia illucens (L.) - Kamau, E.; Mutungi, C.; Kinyuru, J.; Imathiu, S.; Tanga, C.; Affognon, Hippolyte D.; Ekesi, S.; Nakimbugwe, D.; Fiaboe, K.K.M. (Elsevier, 2018)
Edible insects are part of the diets of a significant proportion of rural populations in the tropics especially Africa and Asia, and their use as source of key nutrients for better nutrition is re-emerging. Indigenously, elemental methods are used to process the insects before they are consumed or sold in retail outlets. In recent years, better knowledge of processing, packaging and storage has become necessary because of commercialisation needs. A common processing approach involves drying after a brief heat-treatment step, and then milling into a powdered product which is sold to manufacturers or consumers as ingredient for processing final products. The hydration properties of dried powders of edible house cricket and black soldier fly larvae (BSFL) were studied with the aim of predicting shelf-life stability under typical packaging and storage temperatures experienced in the tropics. Moisture adsorption isotherms were determined gravimetrically at 25, 30 and 35 °C, over 0.11–0.97 water activity (aW) range, and the data fitted to various models. Sorption isotherms were of type II according to Brunauer classification indicating monolayer-multilayer sorption behaviour. Cricket powder exhibited higher hydration capacity, and aW of this product was less sensitive to temperature variation as compared to BSFL powder. In the two products, water exhibited transitions from bound- to free- state at ~5 g/100 g moisture content. Based on Heiss-Eichner model, a shelf-life of 7 months at 25 °C can be achieved if the cricket and BSFL powders are dried to ca. 5 g/100 g moisture content and packaged in 80 μm thick polyethylene films. At 35 °C the shelf-life of the cricket product is shortened three- to four-fold whereas the BSFL powder is unable to store.